The impact of Next-Generation Broadband: Marriage rates and Assortative mating - Miriam Marcén; Marina Morales (Global Labor Organization (GLO), 2025)
This work examines the effect of next-generation broadband on marriage rates among opposite- and same-sex couples in Spain. Given that the decision to sustain a relationship and enter into marriage is influenced by a broad spectrum of opportunities, high-speed broadband access can play a pivotal role in reducing search frictions, enhancing communication, and influencing cultural norms, thereby exerting a positive impact on marriage rates for both homosexual and heterosexual individuals. However, it is not clear whether the magnitude of the impact is the same for both groups. To explore this issue, we exploit plausible exogenous geographic and temporal variations in next-generation broadband coverage. We merge microdata on all Spanish marriages from 2013 to 2022 with the annual proportion of households with access to next-generation broadband via Fiber-to-the-Home (FTTH) at the municipal level. Our findings indicate that an increase in local FTTH coverage is associated with a higher crude marriage rate, controlling for municipality and time fixed effects. The response of same-sex marriages is twice as large as that of heterosexual marriages, relative to their respective average marriage rates. Empirical evidence does not support improved positive assortative mating as an explanation for the differing response observed among same-sex couples. High-speed internet access reinforces positive assortative mating by education and occupation for opposite-sex couples. Supplementary analysis, using data on public funding, shows that government support for expanding FTTH through the Next Generation Broadband Expansion Programme translates into an increase in the crude marriage rate, highlighting the appeal of areas with high-speed internet in addressing depopulation.
Keywords: J12; O33; L96; 330; Next-generation boradband; Fiber-to-the-Home; Marriage rates; Same-sex couples; Public Policies